The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4049/jimmunol.175.10.6786
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Protective Role of Human Group IIA Phospholipase A2 against Experimental Anthrax

Abstract: Anthrax is an acute disease caused by Bacillus anthracis. Some animal species are relatively resistant to anthrax infection. This trait has been correlated to the extent of the local inflammatory reaction, suggesting innate immunity to be the first line of defense against B. anthracis infection in nonimmunized hosts. Group IIA secreted phospholipase A2 (sPLA2-IIA) is produced in particular by macrophages and possesses potent antibacterial activity especially against Gram-positive bacteria. We have previously s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 48 publications
0
55
0
Order By: Relevance
“…In a transgenic mouse model, sPLA2-IIA has been shown to protect animals from i.p. or pulmonary infections by S. aureus or Bacillus anthracis, respectively (17)(18)(19). However, these transgenic mice are artificial models with constitutive overexpression of sPLA2-IIA (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a transgenic mouse model, sPLA2-IIA has been shown to protect animals from i.p. or pulmonary infections by S. aureus or Bacillus anthracis, respectively (17)(18)(19). However, these transgenic mice are artificial models with constitutive overexpression of sPLA2-IIA (36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this enzyme represents a major actor in innate host defense against bacterial infections (12), in particular, by Gram-positive (G + ) bacteria that are highly susceptible to killing by sPLA2-IIA (13)(14)(15)(16). Previous studies showed that constitutively expressed human sPLA2-IIA protected transgenic mice from G + bacterial infections (16)(17)(18)(19).…”
Section: R Espiratory Infections Caused By Staphylococcus Aureusmentioning
confidence: 99%
“…The availability of antibacterial enzymes for the treatment of anthrax, however, may prove valuable, particularly against antibiotic-resistant strains for which no treatment may be available. Recent reports indicate that such an approach can be used to treat experimental infections with B. anthracis using phospholipase A 2 (35) or Bacillus cereus using phage lysin (38) when enzyme is administered shortly after infection. CapD, while not directly bactericidal, facilitates host cell phagocytic killing of encapsulated bacilli, possibly by exposing pathogen-associated molecular patterns and promoting complement deposition on the bacterial surface.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this substrate specifi city, the highly cationic nature of sPLA 2 -IIA, which is not shared with other sPLA 2 s, is essential for bacterial membrane hydrolysis by this enzyme ( 51,52 ). As such, PLA2G2A -transgenic mice, or wild-type mice treated with recombinant sPLA 2 -IIA, are resistant to pneumonia and sepsis following bacterial infection ( 31,32,(53)(54)(55). For this reason, sPLA 2 -IIA can be regarded as a "bactericidal sPLA 2 ."…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%